(untitled) - Nolte, John (St. Louis, MO, 1999)
Univ. of Arizona, Tucson. Introductory neuroanatomy text for medical students. Describes the structure and function of the brain and nervous system. Full-color illustrations and images portray structure-function processes and brain activity. Includes a new chapter on electrical signaling. Previous edition: c1993. DNLM: Nervous System--anatomy & histology.
Keywords: Neuroanatomy,Brain,Nervous System,Giải phẫu học thần kinh,Não,Hệ thần kinh; Anatomy,Anatomy & histology,Giải phẫu,Mô và giải phẫu